Menemukan Kunci Kinerja: Pengaruh Kemampuan dan Usaha dengan Mediasi Dukungan Manajemen - Ariastuti, Fita; Sutianingsih, Sutianingsih (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to understand the influence of ability and work effort on employee performance which is mediated by management support. This type of research applies quantitative descriptive and data collection techniques from questionnaires. The sample was 60 employees of UD. Gemah Ripah, Pacitan Regency. Sampling was carried out using purposive sampling. The data analysis methods used include validity tests, reliability tests, and classic assumption tests, which consist of normality tests, multicollinearity tests, and heteroscedasticity tests. To test the hypothesis, use the Path Analysis and R2 tests using the SPSS Version 25 computer program. Based on the research results, it show that (1) Ability and Work Effort have a positive impact on Employee Performance at UD. Gemah Ripah Pacitan Regency. (2) Ability has a positive impact on management support but work effort does not have a positive impact on management support at UD. Gemah Ripah, Pacitan Regency. (3) Management Support does not have a positive impact on employee performance at UD. Gemah Ripah, Pacitan Regency. (4) Ability has a positive impact on performance but work effort does not have a positive impact on performance which is mediated by management support at UD. Gemah Ripah, Pacitan Regency.